Deposition and metabolism of inhaled ciclesonide in the human lung - Nave, Ruediger; Watz, H.; Hoffmann, Hans; Boss, H.; Magnussen, H. (The European respiratory journal, 2010)
Ciclesonide is an inhaled corticosteroid, administered as a prodrug via a metered-dose inhaler. Following deposition in the lung, ciclesonide is hydrolysed by esterases to form the pharmacologically active metabolite desisobutyryl-ciclesonide (des-CIC). Formation of des-CIC, as well as reversible esterification of des-CIC with fatty acids, has been demonstrated in vitro. The aim of this study was to investigate the in vivo metabolism of ciclesonide in the human lung. - This single-dose, open-label, nonrandomised study was performed in 20 patients undergoing planned lung surgery for treatment of malignant pulmonary lesions. Patients inhaled a single dose of 1,280 μg ciclesonide at various time-points between 2 and 24 h prior to lung tissue resection. The concentration of ciclesonide, des-CIC and fatty acid conjugates of des-CIC in tissue samples was determined. Serum samples for pharmacokinetic analysis were taken at several time-points after inhalation. - The pharmacokinetics in serum indicated that the inhalation by the patients was adequate. Metabolites (des-CIC, des-CIC oleate and des-CIC palmitate) were detected in the resected central and peripheral lung tissues. A substantial portion of ciclesonide was already activated to des-CIC at the first time-point of tissue analysis. - Activation of ciclesonide and formation of des-CIC fatty acid conjugates was confirmed in vivo in the human lung.
Gesehen am 05.05.2023